Evaluation of Antidiarrhoeal activity of extract from roots of Rumex hastatus (Family: Polygonaceae) on experimental animals - Shakuntala, Pushp Bharti, Neetu Sachan, Phool Chandra, Kavita Gahlot (Journal of Applied Pharmaceutical Science)
Rumex hastatus is fairly common small shrub, growing on dry slopes, rocks and walls between 700-2500 m, typically in North Indian hill station. Roots of Rumex hastatus have been used in Ayurveda and other folk medicines for the treatment of diarrhoea. To justify its folklore, present study was undertaken to investigate the antidiarrhoeal activity of the ethanolic extract from the roots of Rumex hastatus (EERH). Preliminary phytochemical screening, acute toxicity study and antidiarrhoeal activity of were studied on castor oil induced diarrhoea and normal gastrointestinal models of rats at 100, 150 and 200mg/kg body weight. The preliminary phytochemical screening of the ethanolic extract from the roots of Rumex hastatus (EERH) results with the presence of anthraquinone glycoside, tannins, flavonoids etc., LD50> 2000mg/kg. The doses of EERH significantly decreased (P
Keywords: Rumex hastatus, Polygonaceae, Loperamide, Atropine.